A 10 GHz inductorless active SiGe HBT lowpass filter. Issue 9 (24th October 2018) - Centurelli, Francesco; Monsurrò, Pietro; Trifiletti, Alessandro
Abstract: High‐frequency (around 10 GHz) filters are necessary for many applications, in anti‐aliasing filters for high‐speed data converters or optical communications. Modern SiGe technology allows implementing radio‐frequency circuits up to about 100 GHz. At the lower frequencies around 10 GHz, the size of passive components is a concern, and inductorless designs are used. We present a topology for an inductorless lowpass biquad filter capable of operating at 10 GHz or more in the STMicroelectronics BiCMOS55 process. The filter is simulated considering temperature, process, biasing and mismatch variations, tested with parametric and Monte Carlo simulations. The layout of the biquad filter has been implemented, and the results of post‐layout simulations are reported. The biquad stage has good dynamic range (45 dB) and power efficiency (0.65 pW/Hz/pole) with respect to comparable active lowpass filters reported in the literature, and, unlike other filters, only uses NPN devices, which are the only high‐speed devices available in many Hybrid Bipolar Transistor (HBT) technologies.